2021
DOI: 10.1371/journal.pbio.3001136
|View full text |Cite
|
Sign up to set email alerts
|

Plant pathogens convergently evolved to counteract redundant nodes of an NLR immune receptor network

Abstract: In plants, nucleotide-binding domain and leucine-rich repeat (NLR)-containing proteins can form receptor networks to confer hypersensitive cell death and innate immunity. One class of NLRs, known as NLR required for cell death (NRCs), are central nodes in a complex network that protects against multiple pathogens and comprises up to half of the NLRome of solanaceous plants. Given the prevalence of this NLR network, we hypothesised that pathogens convergently evolved to secrete effectors that target NRC activit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
144
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 101 publications
(211 reference statements)
3
144
0
Order By: Relevance
“…To challenge this hypothesis, we performed site-directed mutagenesis of the MHD motif predicted in the NB-ARC domain of NRCX. Previously, we showed that histidine (H) to arginine (R) or aspartic acid (D) to valine (V) substitutions within the MHD motif confer autoactivity to the NRC helpers NRC2, NRC3 and NRC4 (Derevnina et al, 2021). Therefore, we first introduced the HR and DV mutations in NRCX (Fig.…”
Section: Unlike Other Nrc Helpers Mutations In the Mhd Motif Fail To Confer Autoactivity To Nrcxmentioning
confidence: 99%
See 2 more Smart Citations
“…To challenge this hypothesis, we performed site-directed mutagenesis of the MHD motif predicted in the NB-ARC domain of NRCX. Previously, we showed that histidine (H) to arginine (R) or aspartic acid (D) to valine (V) substitutions within the MHD motif confer autoactivity to the NRC helpers NRC2, NRC3 and NRC4 (Derevnina et al, 2021). Therefore, we first introduced the HR and DV mutations in NRCX (Fig.…”
Section: Unlike Other Nrc Helpers Mutations In the Mhd Motif Fail To Confer Autoactivity To Nrcxmentioning
confidence: 99%
“…S6). It should be pointed out that although NRC2, NRC3 and NRC4 redundantly contribute to effector-activated Sw-5b hypersensitive cell death (Wu et al, 2017), we recently showed that an autoactive mutant of Sw-5b (Sw-5b D857V ) signals only through NRC2 and NRC3 (Derevnina et al, 2021). Therefore, we conclude that knocking-down of NRCX enhances the activities of NRC2-and NRC3-dependent NRC-S, but doesn't affect the activity of NRC-S that are only dependent on NRC4, as well as other NLR outside the NRC network.…”
Section: Rna Interference Of Nrcx Enhances Nrc2-and Nrc3-dependent Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of PLOS Biology, the Kamoun group [7] provide some of the first evidence of parasitic effectors interfering with helper NLR-mediated cell death (Fig 1). Using an effectoromics screen with a library consisting of a total of 165 effectors from bacteria, oomycete, nematode, and aphid, they have identified 5 effectors that can suppress the cell death induced by 2 NRC-dependent sensor NLRs, Prf or Rpi-blb2, in Nicotiana benthamiana plants.…”
mentioning
confidence: 99%
“…Using a combination of yeast two-hybrid (Y2H), in vitro and in planta assays, the Kamoun group [7] revealed that SS15 and AVRcap1b effectors may suppress NRC2 and NRC3 functions through distinct mechanisms. The SS15 effector directly associates with NRC2 and NRC3 through the NB-ARC domain.…”
mentioning
confidence: 99%